2022
DOI: 10.1007/s00167-022-06964-x
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of complications after derotational femoral and/or tibial osteotomies in patellofemoral disorders in adolescents and active young patients: a systematic review with meta-analysis

Abstract: Purpose To quantify the risk of perioperative and postoperative complications of derotational femoral and/or tibial osteotomies in patellofemoral disorders (anterior knee pain and patellar instability) in adolescents and active young patients. Methods MEDLINE, EMBASE, Cochrane and Scopus databases were used to identify studies published from database inception and June 30, 2021. Meta-analysis was performed to pool the rates of complications related to femur and tibia osteotomies. Values of proportion of compli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…A previous systematic review investigating complications after DeDFO concluded that the procedure is safe both for patellofemoral instability and for anterior knee pain [ 38 ], the former being observed in the present study as well. Another, more recent systematic review of six studies investigating outcomes and satisfaction found very similar results but concluded that there is no consensus on when to perform a DeDFO [ 55 ].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…A previous systematic review investigating complications after DeDFO concluded that the procedure is safe both for patellofemoral instability and for anterior knee pain [ 38 ], the former being observed in the present study as well. Another, more recent systematic review of six studies investigating outcomes and satisfaction found very similar results but concluded that there is no consensus on when to perform a DeDFO [ 55 ].…”
Section: Discussionsupporting
confidence: 79%
“…Previous systematic reviews demonstrated the safety of the procedure with very low complication rates but also included DeDFO for patellofemoral pain [ 38 ]. A more recent systematic review demonstrated favourable results and a low redislocation rate but only included six studies [ 55 ]; however, both reviews included less than 200 patients.…”
Section: Introductionmentioning
confidence: 99%
“…Patellofemoral instability (PFI), anterior knee pain due to patellofemoral maltracking and posttraumatic torsional deformities are the most common indication for torsional (= de‐rotational) corrections around the knee joint [8, 10, 25, 31]. In cases of PFI, a combination of bony deformities is common: dysplasia of the trochlea, lateralization of the tibial tubercle, patella alta or torsional deformity of the femur, the tibia or both [5, 7, 14, 26].…”
Section: Introductionmentioning
confidence: 99%
“…In the presence of femoral maltorsion as an underlying deformity for recurrent patellofemoral instability, rotational osteotomy in combination with patellofemoral stabilising techniques can be performed with a satisfactory outcome [7,12,30]. However, realignment procedures in combination with a trochleoplasty, as often required in high-grade dysplastic knees, are invasive, and associated complications have been reported in up to 40% of cases [18,23]. Therefore, careful selection of patients and comprehensive analysis of underlying concomitant deformities are indispensable for improving clinical outcomes [31].…”
Section: Introductionmentioning
confidence: 99%